Psychological disorders associated with women after abortion - Nihayet Abdulla Sheck; Vian Haji Rasul; Moaid Ismail Jarjis2 (Zanco Journal of Pure and Applied Sciences, 2023)
The researcher's aimed in their current research to identify the levels and the significant of the difference of psychological disorders of women after abortion for (150) participants in Erbil city. Taking into consideration variables such as ages among (5) groups {(21 - 25), (26 - 30), (31 - 35), (36 - 40), (41 & more)}, then number of miscarriages among (3) groups {(1 -2), (3 - 4), (5 & more)} and academic achievement among (4) groups {(Illiterate), (Middle school & less), (Secondary), (Diploma & higher)}. To measuring the Variable's in current researcher's prepared the items of psychological disorders and its (5) dimensions (anxiety, depression, phobia , guilt, OCD) depended on Mental Health Literature after translating the scale according to the need of the research, the validity and reliability of scale were verified. The, (% 90.90 ) of experts agreed on all items of the scale, and the researcher's relied on the Split-half and Cronbach's Alpha methods to record the scales reliability, the results showed that the reliability value of psychological disorders is (0.83) (0.80) respectively. After that the scale were applied on the research samples through individual interviews, and then data processing by using (Spss) the results showed: 1. The prevalence rate of psychological disorders and all dimensions (anxiety, depression, phobia , guilt, OCD) are high and significant among participant's women after abortion in Erbil city. 2. There are significant differences in the prevalence rate of psychological disorders and all dimensions (anxiety, depression, phobia, OCD) according to the variable of age groups among participant's women after abortion , except for the dimensions of guilt it is not significant. 3. There are significant differences in the prevalence rate of psychological disorders and all dimensions (anxiety, depression, phobia, guilt, OCD) according to the variable of number of miscarriage's groups among participant's women after abortion. 4. There are no significant differences in the prevalence rate of psychological disorders and all dimensions (anxiety, depression, phobia, guilt, OCD) according to the variable of academic achievement groups among participant's women after abortion. Depending on these results, the researchers has presented some recommendations and suggestions.